Cosmological constraints on primordial black holes - Cangialosi, Antonino (2019)
Primordial Black Holes (PBH) may have formed from collapse of high-density primordial fluctuations in the early Universe. Interest for PBH has been stirred anew by the LIGO detection of gravitational waves from massive black hole mergers which might be of primordial origin. In this thesis, we discuss how primordial fluctuations are produced from vacuum fluctuations, which get stretched out of causal contact by an early inflationary epoch. Later, we discuss the thresholds above which these perturbations could end up in forming black holes once re-entered in causal contact. PBHs are distinct from those black holes of stellar origin precisely because the formation proceed through a top-down accretion of structure. PBHs are expected to form before the recombination era—the moment in the cosmic history when atoms came into being for the first time—thus, defying the mass bounds from the nuclear processes due to the exotic state of primordial matter. Finally, we present current observational constraints on the abundance and mass spectrum of PBHs.